The Organization of Turns in the Disagreements - qizi, Nusratullaeva Shokhista Sabirjon (Research Parks Publishers, 2023)
The article deals with the study of the speech act of disagreement in the modern pragmatic theory of the English language. The studied problems in the field of pragmatics, and in particular, the speech act of disagreement, are undoubtedly important and relevant in connection with the development of communicative linguistics, which is based on the study of communicative competence, which is the internal ability and readiness of an individual to carry out a speech act of communication in a foreign language.